The endocrine disruptor chlorpyrifos alters hypothalamic Npy and Agrp expression via ERβ-dependent regulation in vitro and in vivo - Pastorino, Monica; Desiderio, Antonella; Perrella, Erica; Campitelli, Michele; Nigro, Cecilia; Peluso, Teresa; De Felice, Mario; Ambrosino, Concetta; Beguinot, Francesco; Miele, Claudia; Raciti, Gregory Alexander (Frontiers in Endocrinology, 2026)
IntroductionObesity represents a global health concern, with the hypothalamus playing a central role in regulating energy balance. Chlorpyrifos (CPF), a widely used organophosphate pesticide, is now recognized as an endocrine-disrupting chemical (EDC). Although the peripheral metabolic effects of CPF are relatively well characterized, its potential impact on central energy balance remains to be investigated. Here, we examined, both in vitro in murine hypothalamic cells and in vivo in murine hypothalami, whether CPF modulates the orexigenic mediators Neuropeptide Y (Npy) and Agouti-related peptide (Agrp). We further explored the molecular mechanisms underlying this regulation.MethodsFor in vitro studies, murine mHypoE-N46 hypothalamic cells were treated with CPF (1 pM) under acute (4 h) and chronic (6-day) exposure conditions. For in vivo studies, hypothalamic tissue from CD-1 mice chronically exposed to CPF (10 mg/kg/day), from conception to 6 months of age while maintained on a standard diet, were analyzed. Gene and protein expression levels, as well as neuropeptide secretion, were assessed by qPCR, Western blotting, and ELISA, respectively. Selective pharmacological antagonists of ERβ and ERα were employed to determine receptor-specific effects.ResultsBoth acute and chronic CPF exposure significantly increased Npy and Agrp mRNA expression and secretion in mHypoE-N46 cells. Chronic CPF treatment selectively upregulated ERβ at the mRNA and protein levels, whereas ERα was unaffected. Pharmacological inhibition confirmed ERβ as the main mediator of CPF action. Consistently, in vivo hypothalamic samples from CPF-exposed mice displayed increased Npy and Agrp expression and an elevated ERβ/ERα ratio, mirroring the in vitro findings. Also, CPF exposure increased leptin receptor (Lepr) expression both in vitro and in vivo.ConclusionOur findings indicate that CPF acts as a central endocrine disruptor by shifting estrogen receptor signaling toward ERβ dominance, thereby promoting orexigenic neuropeptide expression. Together with the increased Lepr expression, this mechanism may contribute to hypothalamic dysfunction and metabolic imbalance. The evolutionary conservation of hypothalamic circuits suggests that similar mechanisms may operate across species and impact metabolic health.